Distribution of Soft Ticks and Their Natural Infection with Borrelia in a Focus of Relapsing Fever in Iran - Z Aghighi; M Assmar; N Piazak; E Javadian; MA Seyedi Rashti; EB Kia; Y Rassi; H Vatandoost (Tehran University of Medical Sciences, 2007)
Tick-borne diseases such as relapsing fever and Crimean-Congo Hemorrhagic Fever (CCHF) are of public health impor¬tance in Iran. There are 471 reported cases of relapsing fever in 2003, according to the Ministry of Health of Iran.The num¬ber of cases has been increased in recent years. Its distribution is more or less prevalent in different parts of Iran. The aim of this study was to find out the fauna and natural infection of soft ticks with Borrelia in Qazvin Province, during their sea¬sonal activity. The province covers 15821 km² between 48-45 to 50-50 east of Greenwich Meridian of longitude and 35-37 to 36-45 north latitude of the equator. For this purpose a field study was carried out in the region. A total of 54 villages from 19 districts were selected ran¬domly and ticks were collected from their habitats according to the standard method. A total of 3197 Argasidae ticks were collected from human dwellings, poultry and animal shelters. They belonged to Argas and Or¬nithodoros genera which 36.8% were Argas persicus, 4% A. reflexus, 6.4% O. canestrini, 45.5% O. lahorensis and 7.3% O. tholozani. It should be noted that 12 ticks of O. erraticus were collected from 12 rodents borrows. We found that 8.82 % of O. tholozani ticks were infected with Borrelia persica and half of the O. erraticus were infected with Borrelia microti. All the people who are in¬volved with veterinary activities should be aware of disease transmission by the ticks. In the endemic area of the disease tick control is recommended.